2017
DOI: 10.1111/bjd.15458
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐32 is highly expressed in lesions of hidradenitis suppurativa

Abstract: Our findings suggest that IL-32 is overexpressed in HS. Targeting IL-32 may therefore represent a new therapeutic option for the treatment of this recalcitrant disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 53 publications
(117 reference statements)
3
60
0
4
Order By: Relevance
“…To this end, we investigated the expression of LL‐37 and CAMP in HS, PS, AD and healthy skin by immunohistochemistry and semi‐quantitative real‐time PCR and compared whether LL‐37 peptide and CAMP mRNA levels correlate with lesional HS skin. In addition, we examined what kind of cells (T cells, macrophages and neutrophils) and cytokines (IFN‐γ, IL‐17, IL‐23, IL‐32, IL‐1β, TNF‐α and IL‐10), which are known to be elevated in HS correlate with the presence of LL‐37. To complete our analysis, we investigated the impact of LL‐37 on the proliferation of lectin‐stimulated CD4 + and CD8 + T cells isolated from the blood of healthy donors and patients with HS and delineated by calcium assay, how LL‐37 impacts proliferation of T cells directly.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we investigated the expression of LL‐37 and CAMP in HS, PS, AD and healthy skin by immunohistochemistry and semi‐quantitative real‐time PCR and compared whether LL‐37 peptide and CAMP mRNA levels correlate with lesional HS skin. In addition, we examined what kind of cells (T cells, macrophages and neutrophils) and cytokines (IFN‐γ, IL‐17, IL‐23, IL‐32, IL‐1β, TNF‐α and IL‐10), which are known to be elevated in HS correlate with the presence of LL‐37. To complete our analysis, we investigated the impact of LL‐37 on the proliferation of lectin‐stimulated CD4 + and CD8 + T cells isolated from the blood of healthy donors and patients with HS and delineated by calcium assay, how LL‐37 impacts proliferation of T cells directly.…”
Section: Introductionmentioning
confidence: 99%
“…Although the γ and β isoforms have been associated with anti‐inflammatory functions including reduced cell activation and proliferation, cytotoxic function and increased IL‐10 production, the majority of studies define a proinflammatory character for IL‐32 . Finally, IL‐32 has been proposed as a biomarker of skin inflammation in AD, alopecia areata and hidradenitis suppurativa . The analysis of IL‐32 isoforms mRNA expression in skin biopsies from three skin disorders (hidradenitis suppurativa, psoriasis and AD) compared with skin from healthy donors, revealed that all main IL‐32 isoforms are expressed in skin, but at different levels depending on the origin of skin disorder .…”
Section: Discussionmentioning
confidence: 99%
“…IL-32 production in the skin has been observed in inflammatory skin disorders such as AD, alopecia areata and hidradenitis suppurativa, suggesting that IL-32 production plays a critical role in skin diseases. 10,11,26 To improve the understanding of molecular mechanisms that allow LC activation in the epidermal layers, we have investigated the role of IL-32 in the epidermis. We first showed that KCs are the major cell population that produces IL-32 in the skin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations